2017
DOI: 10.1002/jctb.5293
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous production of C‐phycocyanin and extracellular polymeric substances by photoautotrophic cultures of Arthrospira platensis

Abstract: BACKGROUND: Arthrospira platensis produces the blue pigment C-phycocyanin (C-PC) and extracellular polymeric substances (EPS) of potential value in food and pharmaceutical applications. RESULTS: Batch cultures were used to simultaneously produce C-PC and EPS. The effects of incident light level on growth and product formation are reported. A maximum biomass concentration of 1.5 g L −1 in 14 days was obtained at a light intensity of 203 mol m −2 s −1 . The light intensity affected the biomass composition and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…Between the different light conditions, the highest phycocyanin content was obtained under LL, followed by NL, while HL gave significantly lower values. These results are in agreement with previous observations that both a reduction in the light quantity and change in light quality (light spectrum towards red) can induce an increase in the phycocyanin concentration in Arthrospira biomass. This observation can be explained by the capacity of chromatic adaptation of many cyanobacteria, including Arthrospira , in which cyanobacteria adjust their pigment composition in response to light alterations .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Between the different light conditions, the highest phycocyanin content was obtained under LL, followed by NL, while HL gave significantly lower values. These results are in agreement with previous observations that both a reduction in the light quantity and change in light quality (light spectrum towards red) can induce an increase in the phycocyanin concentration in Arthrospira biomass. This observation can be explained by the capacity of chromatic adaptation of many cyanobacteria, including Arthrospira , in which cyanobacteria adjust their pigment composition in response to light alterations .…”
Section: Resultssupporting
confidence: 93%
“…Similarly, in the NL runs, the protein content increased from 53% in the control culture to 58% in the red and 65% in the grey light filter cultures. So far, there are several studies suggesting that the protein content is subject to changes in the light intensity and/or spectral composition of the light . In the study by Dejsungkranont et al , the proteins in Arthrospira biomass were decreased from 23 to 15% with increasing light intensities (from 101 to 203 μmol m −2 s −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PFD did not have any positive effect on EPS production, its interaction with NaCl concentration provided a 0.98 g.g -1 yield in EPS. On the other hand, Dejsungkranont, Chisti, & Sirisansaneeyakul (2017) studying the effect of PFD on the production of EPS by Arthrospira platensis observed that the highest level of PFD of 203 μE.m -2 .s -1 favored EPS production (956.4 ± 37.3 mg.L -1 ) as well as biomass (1.5 g.L -1 ). Under the smallest value of PFD of 101 μE.m -2 .s -1 , 0.8 g.L -1 of biomass and 637.3 ± 41.3 mg.L -1 of EPS were obtained.…”
Section: Final Biomass Concentration and Eps Yield Under Different Grmentioning
confidence: 99%
“…Challouf et al (2011) described the antibacterial activity against Salmonella typhimurium and Staphylococcus epidermis. Also, the antioxidant activity from crude EPS was studied by Dejsungkranont et al (2017).…”
Section: Introductionmentioning
confidence: 99%